PEMBERDAYAAN PERAJIN SAPU IJUK DI KOTA SEMARANG - Suwahyo, Suwahyo; Widodo, Rahmat Doni (Universitas Negeri Semarang, 2017)
The purpose of this activity is to solve the problems faced by Mitra IbM who strive in the creative industry, in this case the palm fiber broom. IbM partner’s location is located in the center of the broomstick industry in Kel. Wonolopo, Mijen Sub-district of Central Java. There are two aspects of the problem to be addressed, namely aspects of production and management aspects. As the implementation team this activity involves lecturers and students with areas of expertise in accordance with the needs of the field. In the implementation, several methods are used to support each other, such as lectures for theoretical and motivational materials, demon- strations / demonstrations to deliver practice materials / skills, hands-on practices by partners, and mentoring activities. The results of this activity among others are: 1) Produced one unit of circle sawing machine, 2) Produced one unit of dowel machine, 3) The quality and design of broom increased, 4) The application of business bookkeeping, 5) The existence of labels and product promotion, 6) Product marketing increased, 7) Income and business turnover increased